Clinical characteristics, diagnosis, outcomes and lung microbiome analysis of invasive pulmonary aspergillosis in the community-acquired pneumonia patients - Min Deng; Huan Xu; Zhi Ao; Mengqi Li; Huifang Liu; Yuliang Liu (BMJ Open Respiratory Research)
Background Invasive pulmonary aspergillosis (IPA) remains underestimated in patients with community-acquired pneumonia (CAP). This study aims to describe clinical features and outcomes of IPA in CAP patients, assess diagnostic performance of metagenomic next-generation sequencing (mNGS) for IPA and analyse lung microbiome via mNGS data.Methods This retrospective cohort study included CAP patients from 22 April 2019 to 30 September 2021. Clinical and microbiological data were analysed. Diagnostic performance of mNGS was compared with traditional detection methods. The lung microbiome detected by mNGS was characterised and its association with clinical features was evaluated.Main results IPA was diagnosed in 26 (23.4%) of 111 CAP patients. Patients with IPA displayed depressed immunity, higher hospital mortality (30.8% vs 11.8%) and intensive care unit mortality (42.1% vs 17.5%) compared with patients without IPA. The galactomannan (GM) antigen test had the highest sensitivity (57.7%) in detecting the Aspergillus spp, followed by mNGS (42.3%), culture (30.8%) and smear (7.7%). The mNGS, culture and smear had 100% specificity, while GM test had 92.9% specificity. The microbial structure of IPA significantly differed from non-IPA patients (p<0.001; Wilcoxon test). Nineteen different species were significantly correlated with clinical outcomes and laboratory biomarkers, particularly for Streptococcus salivarius, Prevotella timonensis and Human betaherpesvirus 5.Conclusions Our results reveal that patients with Aspergillus infection tend to have a higher early mortality rate. The mNGS may be suggested as a complement to routine microbiological test in diagnosis of patients at risk of Aspergillus infection. The lung microbiota is associated with inflammatory, immune and metabolic conditions of IPA, and thus influences clinical outcomes.